(Un)veiling Bodies. A Trajectory of Chilean Post-dictatorship documentary. - Pinto Veas, Iván (Imagofagia, 2021)
Sobre Elizabeth Ramírez-Soto. (Un)veiling Bodies. A Trajectory of Chilean Post-dictatorship documentary. Oxford: Legenda, 2019, 219 pp., ISBN 978178-188-701-1.